Effect of foliar chelated forms spraying on grape yield and mineral status of shoots - Poposka, Hristina; Mukaetov, Dusko (Bulgarian Journal of Crop Science, 2024)
The aim of this study was to evaluate the foliar chelated forms of Mg and Fe, on grape yield and mineral status of the shoots of vine cultivar Cardinal. Field trials were organized using a random block system with three variants, including a control (Variant I), each replicated three times. Foliar fertilizers were applied at a concentration of 0.5% on four occasions throughout the vegetation period: before and after blooming, during buckshot berry stage, and at the verasion stage. Over the ivestigation of three years, the application of foliar Mg and Fe fertilizers significantly influenced grape yield. The variant treated with Fe (VFe) demonstrated a higher average yield of 14.87 t/ha. Furthermore, a noticeable impact of foliar fertilizers on the concentration of analyzed elements in grapevine shoots was observed. Over the three-year period, the average content of macro elements, including nitrogen, phosphorus, calcium, magnesium, and iron, was higher in the treated variants compared to the control. Additionally, results from shoot tissue analysis confirmed the existence of an antagonistic relationship between magnesium and potassium.
Keywords: grape; Cardinal; foliar; chelated; shoot; elements